Broadband multilayer optics for ultrafast EUV absorption spectroscopy with free electron laser radiation. (30th January 2015) - Corso, A J; Zuppella, P; Principi, E; Giangrisostomi, E; Bencivenga, F; Gessini, A; Zuccon, S; Masciovecchio, C; Giglia, A; Nannarone, S; Pelizzo, M G
Abstract: A new experimental approach for near–edge ultrafast absorption spectroscopy in the extreme ultraviolet (EUV) spectral region at the FERMI@Elettra EIS-TIMEX end-station is presented. An innovative multilayer mirror is proposed as the key element of the set-up. The multilayer structure is a tailor-made Mo/Y periodic stack tuned at the 12.2–12.6 nm wavelength range, designed and realized to probe matter under extreme conditions by focusing the tunable free electron laser radiation, without affecting the temporal beam properties. The performance of such coated mirrors has been investigated at FERMI@Elettra EIS-TIMEX and the results have been compared with those obtained using synchrotron light. Further, the focusing system has been tested by performing sub-100 fs absorption spectroscopy experiments at the L(2, 3)-edge of silicon.